2007
DOI: 10.1637/0005-2086(2007)51[781:iagcoa]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Genetic Characterization of Avian Influenza Viruses and a Newcastle Disease Virus from Wild Birds in Barbados: 2003–2004

Abstract: Zoonotic transmission of an H5N1 avian influenza A virus to humans in 2003-present has generated increased public health and scientific interest in the prevalence and variability of influenza A viruses in wild birds and their potential threat to human health. Migratory waterfowl and shorebirds are regarded as the primordial reservoir of all influenza A viral subtypes and have been repeatedly implicated in avian influenza outbreaks in domestic poultry and swine. All of the 16 hemagglutinin and nine neuraminidas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 30 publications
2
19
0
Order By: Relevance
“…The isolated AIVs included five different HA subtypes (3, 5, 7, 9, and 10) and five NA subtypes (1, 2, 3, 6, and 9) indicating that wild birds in Egypt introduce a wide range of viruses into the Egyptian environment. Similar to previous surveillance studies, 1,23 all isolates were detected in Anseriformes (mallard, teal, pintail, and shoveler).…”
Section: Discussionsupporting
confidence: 88%
“…The isolated AIVs included five different HA subtypes (3, 5, 7, 9, and 10) and five NA subtypes (1, 2, 3, 6, and 9) indicating that wild birds in Egypt introduce a wide range of viruses into the Egyptian environment. Similar to previous surveillance studies, 1,23 all isolates were detected in Anseriformes (mallard, teal, pintail, and shoveler).…”
Section: Discussionsupporting
confidence: 88%
“…Many of these migratory birds have been implicated as carriers of viral pathogens such as AIV, NDV and WNV. One such bird is the blue winged teal, from which AIV and NDV were isolated in Barbados [ 9 ]. In this study no antibodies were detected in the sampled backyard birds against AIV.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that the occurrence of the H5 subtype was not uncommon in AIV monitoring (Hanson et al., 2003; Wallensten et al., 2007; Dusek et al., 2009). Other studies have provided information about the AIV in migratory and resident birds in Argentina, Bolivia and Caribbean countries, and these studies identified H1, H3, H4, H10 and H13 subtypes (Douglas et al., 2007; Spackman et al., 2007a; Pereda et al., 2008; Ghersi et al., 2009; Alvarez et al., 2010). This kind of research can provide valuable information about the species involved in the introduction and circulation of AIV to new areas.…”
Section: Discussionmentioning
confidence: 99%